Kajian Hukum Atas Hubungan Antara Nasabah Dan Bank Ditinjau Dari Undang-Undang Nomor 10 Tahun 1998 Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 Tentang Perbankan - Andriany Widie Astuti; Wahyuni Safitri (Yuriska: Jurnal Ilmiah Hukum, 2020)
The relationship between banks and customers is based on the two most related elements, namely law and trust. A bank can only carry out activities and develop its bank, if the community "believes" to place its money, on banking products that exist in the bank. The higher the trust of the community, the higher the public's awareness to save money with the bank and to use other banking services. Public trust is the main key to the development or failure of a bank, in the sense that without the trust of the community, then a bank will not be able to carry out its business activities. For business people, banks are the main complement in carrying out daily activities, controlling the entry and exit of funds and achieving success, and are usually in the form of checking accounts. Based on this, the writer wants to examine more deeply the relationship between customers and banks regarding account information, bank rights and customer rights, and is associated with existing regulatory regulations.